2002
DOI: 10.1093/annonc/mdf236
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bedside renal function estimates and measured glomerular filtration rate (Tc99mDTPA clearance) incancer patients

Abstract: All the assessed estimates for renal function were found to have significant limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
5
26
1
Order By: Relevance
“…6 -8 However, in several studies in nonrenal patient populations, their predictive performance was disappointing. 9,10 Although several important studies in CHF used renal function estimations by creatinine-based formulas, none of these formulas have been validated in a wide range of CHF patients. A number of factors specific to this group of patients may influence the accuracy and precision of these formulas, such as the predominantly hemodynamic nature of renal function impairment, medication interfering with renal function, sodium retention leading to volume expansion, and loss of muscle mass due to inactivity.…”
Section: Clinical Perspective P 1580mentioning
confidence: 99%
“…6 -8 However, in several studies in nonrenal patient populations, their predictive performance was disappointing. 9,10 Although several important studies in CHF used renal function estimations by creatinine-based formulas, none of these formulas have been validated in a wide range of CHF patients. A number of factors specific to this group of patients may influence the accuracy and precision of these formulas, such as the predominantly hemodynamic nature of renal function impairment, medication interfering with renal function, sodium retention leading to volume expansion, and loss of muscle mass due to inactivity.…”
Section: Clinical Perspective P 1580mentioning
confidence: 99%
“…Moreover, the Martin equation, developed to predict GFR in cancer patients, underestimates GFR in females and overestimates GFR in males (Poole et al 2002). It was suggested that in elderly cancer patients the Wright equation may be the most accurate, precise and least biased equation for the calculation of GFR higher than 50 ml/min (Marx et al 2004).…”
Section: Creatinine Clearance Through 24-h Urine Collection or Mathemmentioning
confidence: 99%
“…For this reason, approaches based on nonlinear mixed effects models, often referred to as population models, have recently been published and independently assessed (Martin et al, 1998;Wright et al, 2001;Poole et al, 2002;Léger et al, 2002). These methods involve the use of patient specific 51 Cr-EDTA plasma data together with supplementary covariate information.…”
mentioning
confidence: 99%